The Business Services Industry in the Context Of Professional Services - the Relationship Approach - Gnusowski , Marek (Studia Oeconomica Posnaniensia, 2026)
The Polish business services (SSC/BPO) market is developing dynamically and is the main frontier of growth in the services sector. It seems that the theoretical grounds of outsourcing business services and professional service firms are contradictory, however, in this paper the common ground between two concepts will be found. It is possible due to evolution in the functioning of business services in Poland. The paper is conceptual and the arguments based upon broadly accepted facts are presented and systematized.